Reseña de Levey, David (2008). Language Change and Variation in Gibraltar - Merino Ferrada, Mª Carmen (Pragmalingüística, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Se trata de una reseña de Levey, David (2008). Language Change and Variation in Gibraltar.